2020
DOI: 10.3390/su13010232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RUSLE and MMF Soil Loss Models and Evaluation of Catchment Scale Best Management Practices for a Mountainous Watershed in India

Abstract: Soil erosion from arable lands removes the top fertile soil layer (comprised of humus/organic matter) and therefore requires fertilizer application which affects the overall sustainability. Hence, determination of soil erosion from arable lands is crucial to planning conservation measures. A modeling approach is a suitable alternative to estimate soil loss in ungauged catchments. Soil erosion primarily depends on soil texture, structure, infiltration, topography, land uses, and other erosive forces like water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The forest, forest scrub, grassland and wetland were set values close to 1 due to the absence of conservation practices, but the presence of vegetative cover in these land uses. The outcomes of the present study authenticate with the findings of Biswas & Pani (2015) for the Jharkhand (Barakar basin) (0-1), Srinivasan et al (2019) for Odisha, India (0-1) and Das et al (2021) for the Nogpoh micro watershed of Ri-Bhoi district of Meghalaya (0.6 to 1). Thus, the presence of anti-erosion practices aids in the reduction of soil disintegration in regions of steeper slants where erosion rates are otherwise comparatively extreme (Imajjane & Belfoul, 2020).…”
Section: P Factorsupporting
confidence: 88%
“…The forest, forest scrub, grassland and wetland were set values close to 1 due to the absence of conservation practices, but the presence of vegetative cover in these land uses. The outcomes of the present study authenticate with the findings of Biswas & Pani (2015) for the Jharkhand (Barakar basin) (0-1), Srinivasan et al (2019) for Odisha, India (0-1) and Das et al (2021) for the Nogpoh micro watershed of Ri-Bhoi district of Meghalaya (0.6 to 1). Thus, the presence of anti-erosion practices aids in the reduction of soil disintegration in regions of steeper slants where erosion rates are otherwise comparatively extreme (Imajjane & Belfoul, 2020).…”
Section: P Factorsupporting
confidence: 88%
“…This index (K value) designates the susceptibility of soil to get erode (Das et al, 2021). It is mainly dependent on the land/soil features, the texture of the soil, organic matter content, and unsaturated hydraulic conductivity.…”
Section: Soil Erodibility Index/factor (K)mentioning
confidence: 99%
“…In a similar study, Das et al (2018) predicted a mean soil loss below 5 t ha -1 year -1 , while Chatterjee (2020) estimated an erosion rate of 3.4 t ha -1 year -1 . On the other hand, Dabral et al (2008), Pandey et al (2009), Das et al (2020), and Barman et al (2020) reported a comparatively higher mean erosion rate of 51, 57.06, 59.94, and 115.4 t ha -1 year -1 , respectively. Such an extensive disparity may be attributed to regional distinctions in the parameters as well as the varying methodology adopted while preparing these parameters.…”
Section: Validationmentioning
confidence: 89%